(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article provides a comprehensive overview of the historical development of the Uzbek script, tracing the transition from Arabic script to Cyrillic, and subsequently to the current Latin alphabet. It also presents a comparative analysis of the phonetic capabilities of Uzbek letters, the distinctive features, and shortcomings of various writing systems. The study draws scientific conclusions based on historical sources, linguistic scholars’ opinions, and practical challenges.